Information literacy as emancipatory resource – case study of patients with Diabetes Mellitus - Nadi Helena Presser (Biblios, 2012)
The information literacy is the ability of a person to mobilize knowledge, skills and attitudes in order to undertake decisions based on information. In the health field, such competence is the patient’s initiative taking in the process of information searching and use, relative to problems caused by certain pathology, as an emancipatory resource and development of their citizenship. This article is a reflection on the theoretical and methodological framework of information literacy in the context of patients with Diabetes Mellitus (DM) treated at the Medical Center Senador José Ermírio de Moraes (MCSJEM), located in the city of Recife, Pernambuco (PE) state, Brazil. From the viewpoint of the selected approach method, the research is qualitatively and quantitatively characterized, in which the primary data were collected by means of semi-structured interviews. Although the treatment of DM requires considerable self-care, due to eventual injuries resulting from complications, the results of this study demonstrate that among the patients surveyed, few of them show abilitys with information that indicate emancipatory capacity.